REGISTER DALAM GRUP ORDER PENGGEMAR SEVENTEEN (CARAT) DI LINE - Irawan, Puspita Sri Mulia Artamefia; Hamida, Layli (Universitas Hamzanwadi, 2025)
The access to South Korean popular culture has been made accessible by the growth of the internet and the widespread use of social media, particularly in Indonesians' interpersonal interactions. This study aims to examine how registers are used in the Seventeen fan community, commonly referred to as Carat, Group Order, and how well-understood registers are used during the transactions within the Group Order. The data for this study were collected via note-taking, interviews, and observation using a digital ethnography research design on the Line digital platform. The findings indicate that the Carat Group Order uses two different kinds of registers: consultative and informal. Additionally, Group Order members believe that to prevent misunderstandings while performing purchases and sales, it is crucial to properly understand the register when performing Group Order transactions. This further illustrates how the values that are present in the Carat community are represented by an understanding of the use of registers in the Group Order.